Signal processing and information technology : Second International Joint Conference, SPIT 2012, Dubai, UAE, September 20-21, 2012, Revised Selected Papers - Elkafrawy, Passent; Das, Vinu V. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Joint Conference in Signal Processing and Information Technology, SPIT 2012, held in Dubai, UAE, in September 2012. The 32 papers included in this volume were carefully reviewed and selected from 330 submissions. The papers cover research and development activities in computer science, information technology, computational engineering, image and signal processing, and communication.